Genetic improvement for the sustainable management of resistance - Craenen, K.; Ortíz, R. (2003)
In the 1990s, innovative cross-breeding and classic genetic analysis of segregation ratios allowed advances in the understanding of host plant response to black leaf streak disease. Partial resistance owing to a recessive major gene (bs1 ) coupled with at least two additive minor genes (bsri ) appears to be durable because this genetic system slows disease development in the host plant. As a consequence, resistant hybrids show more healthy leaves, i.e. greater photosynthetic leaf area, than their susceptible full-sibs, which may partially account for their high yield. Although other breeding approaches such as genetic transformation, mutagenesis and somaclonal variation are advocated to develop new resistance to Mycosphaerella leaf spot diseases in Musa, farmers today are only adopting the research products from the so-called conventional breeding, i.e. tetraploid or triploid resistant hybrids from interspecific interploidy crosses. Recent findings on pathogenicity with molecular and cellular biology tools are providing new knowledge on host plant – pathogen interactions, which may result in science-led approaches for deploying resistance against sigatoka diseases within a holistic integrated disease management framework. For example, cultivar mixtures and gene pyramiding may be alternatives for potential durable resistance to sigatoka diseases of plantain and banana.